Quercetin Suppresses Intracellular ROS Formation, MMP Activation, and Cell Motility in Human Fibrosarcoma Cells. Issue 9 (31st July 2013) - Lee, Dong Eun; Chung, Min‐Yu; Lim, Tae Gyu; Huh, Won Bum; Lee, Hyong Joo; Lee, Ki Won
Abstract: Cell metastasis is a major cause of death from cancer and can arise from excessive levels of oxidative stress. The objective of this study was to investigate whether the natural flavonoid quercetin can inhibit matrix metalloproteinase (MMP)‐2 and ‐9 activities through the attenuation of reactive oxygen species (ROS) formation, an event expected to lead to the inhibition of cell motility. To induce sustained ROS formation, cells were treated with phenazine methosulfate (PMS; 1 μM). Noncytotoxic concentrations of quercetin inhibited PMS‐induced increases in cell motility in HT1080 human fibrosarcoma (HT1080) cells. While nearly 100% of cells were observed to migrate after 24 h of PMS treatment, quercetin significantly ( P < 0.01) suppressed this effect. We also found that quercetin, up to 10 μg/mL, attenuated PMS‐induced MMP‐2 activation. We then investigated whether the decreased levels of MMP‐2 activation could be attributable to lower levels of ROS formation by quercetin. We found that quercetin treatments significantly attenuated PMS‐induced ROS formation ( P < 0.01) and resulted in decreased cell motility associated with a reduction in MMP‐2 and ‐9 activitiy in HT1080 cells, even in the absence of PMS treatment. Collectively, these results suggest that quercetin inhibits cell motility via the inhibition of MMP activation in HT1080 cells in the presence and absence of PMS. This is likely to be a result of the suppression of intracellular ROS formation by quercetin.